2001
DOI: 10.1039/b006796m
|View full text |Cite
|
Sign up to set email alerts
|

Capillary-scale polarimetry for flowing streams

Abstract: A micro-polarimeter with a 40 nL probe volume was configured so that it is compatible with capillary-scale flowing stream analysis. The optical configuration consists of two polarizing optics, a capillary, a laser source and a photodetector which is very simple to configure with low cost components. This unique polarimeter is based upon the interaction of a linearly polarized laser beam and a capillary tube, in this case one with an inner diameter of 250 microns. Side illumination of the tube results in a 360 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…[xli] Detection of optical rotation, α, by laser optical methods and flow techniques is adaptable to HPLC for on- the-fly characterization of chiral molecules. [xlii],[xliii]. Circular dichroism (CD) is observed when circularly polarized light (CPL) passes through a solution of a chiral, optically active compound whose molecular structure contains a chromophore.…”
Section: Chiroptical Techniques: Circular Dichroism and Absolute Cmentioning
confidence: 99%
“…[xli] Detection of optical rotation, α, by laser optical methods and flow techniques is adaptable to HPLC for on- the-fly characterization of chiral molecules. [xlii],[xliii]. Circular dichroism (CD) is observed when circularly polarized light (CPL) passes through a solution of a chiral, optically active compound whose molecular structure contains a chromophore.…”
Section: Chiroptical Techniques: Circular Dichroism and Absolute Cmentioning
confidence: 99%
“…2), or by introducing an optically active solute into the capillary. In this way, CPD can be used to quantify optically active solutes [2][3][4][5] or to determine optical rotary power of an unknown solute [5,6]. It is noteworthy that it has been previously shown that the polarimetry signal is contained within the high-frequency component of the CPD fringe pattern and the spatial frequency of this pattern does not change with concentration of nonoptically active solutes [2,5,6] (e.g., it is relatively insensitive to refractive index changes).…”
Section: Figurementioning
confidence: 99%
“…3B) of the fringe was obtained by using Matrox Inspector image processing software. Then two pixels from the line profile, each corresponding to the maximum and minimum intensity values of an adjacent peak and trough, were used to calculate depth of modulation (DOM) [2,3,5,6] (Fig. 3B):…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations